2021
DOI: 10.1002/er.7385
|View full text |Cite
|
Sign up to set email alerts
|

A facile strategy to construct layered membranes with high and stable proton conductivity based on sulfonated graphene oxide

Abstract: Spin coating as an easy-operation strategy to construct layered membranes has been widely mentioned in the fields of microelectronics, energy storage, and conversion, etc. In this research, the successful construction of proton exchange membranes (PEMs) bearing layered structure consisting of sulfonated graphene oxide (SGO) nanosheets and polyvinyl chloride (PVC) with the spin coating method has been demonstrated by the identification of the multilayered dispersion of components and compact structure. The hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The coating strategy is widely employed in the fabrication of layered membranes and has garnered significant attention. This technique encompasses several methodologies, including dip coating, spin coating, and spray coating, which offer versatility and ease of operation in the preparation process. , These methods rely on the attachment of solute species to a substrate through controlled solvent volatilization . He et al has implemented a sequential coating technique for the formation of highly cohesive and uniform ultrathin 2D composite membranes .…”
Section: Construction Methods Of 2d Composite Membranesmentioning
confidence: 99%
“…The coating strategy is widely employed in the fabrication of layered membranes and has garnered significant attention. This technique encompasses several methodologies, including dip coating, spin coating, and spray coating, which offer versatility and ease of operation in the preparation process. , These methods rely on the attachment of solute species to a substrate through controlled solvent volatilization . He et al has implemented a sequential coating technique for the formation of highly cohesive and uniform ultrathin 2D composite membranes .…”
Section: Construction Methods Of 2d Composite Membranesmentioning
confidence: 99%
“…This represents 6% of the total cumulative emission reductions. The development of hydrogen energy is due to the use of new nanostructured materials, for example, metal-organic frameworks, nanoparticles, carbon structures, and others [ 1 , 2 , 3 , 4 ]. Hydrogen fuel cells are clean conversion energy devices for a variety of applications, such as stationary energy sources, vehicles, and even portable devices [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al 17 reported that the damp heat aging rate significantly impacts the relaxation modulus of the Nafion® 212 membrane, with modulus values increasing over time. Jin et al 18 fabricated layered PEMs using sulfonated graphene oxide (SGO). Their study revealed that the organized arrangement of SGO nanosheets greatly enhanced proton conduction, as evidenced by a proton conductivity value of 3.63 × 10 −2 S/cm at 150°C.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al 17 reported that the damp heat aging rate significantly impacts the relaxation modulus of the Nafion ® 212 membrane, with modulus values increasing over time. Jin et al 18 fabricated layered PEMs using sulfonated graphene oxide (SGO). Their study revealed that the organized arrangement of SGO nanosheets greatly enhanced proton conduction, as evidenced by a proton conductivity value of 3.63 Â 10 À2 S/cm at 150 C. Furthermore, Zhao et al 19 prepared multilayered membranes using the vacuum-assisted flocculation method, resulting in membranes with high and stable proton conductivity even at subzero temperatures.…”
Section: Introductionmentioning
confidence: 99%